Side friction parameters and their influences on capacity of Indian undivided urban streets - Subhadip Biswas; Satish Chandra; Indrajit Ghosh (International Journal of Transportation Science and Technology, 2021)
The primary aim of this research is to analyse the influence of side friction on the capacity of undivided urban streets. Side friction is a composite variable signifying the degree of interaction between regular traffic flow and other surrounding activities. Three elements of side friction were considered in this work viz. on-street parking, pedestrian movements and non-motorized vehicles. The research is based on the data collected from six base sections and ten non-base sections located in different cities of India. To extract side friction data, the carriageway width was divided into ten equal segments by using longitudinal virtual lines. Capacity of both base and non-base sections were estimated using ‘fundamental diagram method’. Relationship between carriageway width and capacity was determined in absence of side friction. Capacity under the influence of side friction was observed significantly lower (up to 60.73%) than the capacity of base section of the same carriageway width. A number of parameters were considered under different side friction elements. Some of these parameters are conceptualized in this study and rest are taken from literature. These parameters were further shortlisted based on statistical measurers, then standardized using ‘feature scaling method’ and finally used as design variables to model the ‘reduction in capacity’. While majority of the previous research efforts were focussed on estimating the influence of side frictional elements on performance of divided urban roads, the model proposed in this study will be useful to find the capacity particularly for undivided urban streets under prevailing side friction conditions.